The effect of organizational culture on trainers' job satisfaction in the Addis Ababa City Administration, Ethiopia - Aklilu Alemu Ambo (Cogent Business & Management, 2024)
This study aimed to examine the influence of organizational culture on job satisfaction among trainers in technical and vocational education and training (TVET) colleges in Addis Ababa City Administration. Utilizing a cross-sectional survey design, a sample of 230 trainers was selected from two colleges through simple random sampling. Standardized questionnaires were employed to collect data on organizational culture and job satisfaction, which underwent analysis using statistical techniques, including frequency, percentage, mean and standard deviation, Spearman's rho correlation, Mann-Whitney U test, and multiple regression analysis with SPSS version 23. The findings revealed that adhocracy was the dominant cultural type in TVET colleges, and trainers expressed satisfaction with their jobs in both institutions. Furthermore, the study identified that organizational culture types explained 30% of trainers' job satisfaction, with market culture emerging as the sole significant and positive predictor of job satisfaction in the area (0.74). Additionally, a weak to moderate positive correlation was observed between organizational culture and trainers' job satisfaction. Notably, a statistically significant difference was noted between male and female trainers regarding job satisfaction. Consequently, the study recommends prioritizing efforts to enhance market culture to sustain trainers' job satisfaction.
Keywords: 650; ddis ababa; cVF; ethiopia; job satisfaction; organizational culture; TVET